m-1=-2/9

Simple and best practice solution for m-1=-2/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-1=-2/9 equation:


m in (-oo:+oo)

m-1 = -2/9 // + -2/9

m-(-2/9)-1 = 0

m+2/9-1 = 0

m-7/9 = 0 // + 7/9

m = 7/9

m = 7/9

See similar equations:

| a+2/3=19/15 | | 25/44=w+3/4 | | k/-4=-3/4 | | a+3/5=63/55 | | m/4=6 | | -7t=7/8 | | a+1/2=-15/2 | | 65/6=x+10 | | 3/8+n=9/8 | | n/2=-1/6 | | m+5/9=-76/9 | | 45/28=d+6/7 | | x+2/9=46/45 | | b/6=4 | | -5w=35 | | 3/7d=-24/77 | | 6d=60 | | t+9=93/10 | | n-1/10=99/10 | | -28/3=a+2/3 | | x+7/9=10/9 | | n/-4=-2/7 | | 5/8+x=35/24 | | 8=n+7 | | a/-7=4 | | n+6=33/5 | | a/3=7 | | m-10=-19 | | b-3/5=-1/5 | | k/3=6 | | d-9=-97/11 | | a-8=-5 |

Equations solver categories